Passing otoacustic emissions as a complementar method in the topodiagnosis of the neurosensories hearing loss - Franceschi, Cacineli Marion de; Tochetto, Tania; Lautenschlager, Larissa (International Archives of Otorhinolaryngology, 2010)
Introduction: To evaluate the otoacustic emissions (EOAETs) in patients with neurosensory hearing loss do not belong to the clinical routine. However it would obtain valuables information concerning the topodiagnosis. Objective: To identify signs of retro cochlear alteration in individuals with neurosensory dysacusis diagnosis. Method: A transversal, observational, quantitative and, prospective study. Were analyzed 34 patients' records of users of the Speech Therapy Attendance Service. In the study were included individuals with neurosensory hearing loss of moderate to deep degree. An evaluation of Passing Otoacustic Emissions (EOAETs) was performed in all the individuals of the sample. Those that do not presented EOAETs had the external and middle ear' condition evaluates through meatoscopy and tympanometry to eliminate ears with sings of conductive alteration. Results: Before that the exclusion criteria were applied, they have remained 13 individuals, totalizing 26 ears: four with hearing loss of moderate degree (15%), four with moderately severe degree (15%), two with severe degree (8%), 15 with deep degree (58%) and, one with deafness (4%). The tympanometric curves found were 22 (85%) Type A and, four (15%) Type C. It was verified the presence of EOAETs in only two ears (8%) of a same individual. Conclusion: It was verified the predominance of the EOAETs absence in individuals with neurosensory hearing loss of moderate to deep degree. In one case the EOAETs were registered, that suggest retrocochlear alteration. Raising suspicion of retrocochlear alterations.